AIR DROP INFECTIONS - Jamolova Nilufar Zayniddin qizi (Web of Journals Publishing, 2023)
Airborne transmission of infectious agents poses a significant threat to public health, particularly in densely populated areas. This article aims to explore the risks associated with air drop infections, examining the literature on airborne pathogen transmission and analyzing potential methods to mitigate these risks. The methods section discusses current prevention strategies, while the results section provides insights into the effectiveness of these measures. The discussion section delves into the implications of the findings and proposes recommendations for future research and public health initiatives.
Keywords: Air drop infections, airborne transmission, pathogen spread, respiratory diseases, environmental factors, public health, prevention strategies.